2022
DOI: 10.21776/ub.ecsofim.2022.009.02.04
|View full text |Cite
|
Sign up to set email alerts
|

The Economic of Mini Purse Seine Fisheries by Season and Fishing Ground in Kei Island

Abstract: The economic profit of mini purse seine fishing business in the coastal area of the Kei Islands is different in every season and fishing ground. The aim.of.this analyze the profit of the mini purse seine fishing business on every season and on fishing grounds. Collecting data using survey methods, determining respondents using purposive sampling. Data were analyzed using fishing ground analysis and economic analysis. The results of.the identification indicate that during the transitional season 1 and west, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…Fishermen utilize various fishing tools in Maluku, including purse seines, or what the Maluku people know better as jaring bobo. Purse Seine (jaring bobo) is a very productive fishing tool (Polhaupessy et al, 2019;Picaulima et al, 2022) and is found in almost every area in Maluku. The operation of this fishing gear is generally carried out by fishermen in Maluku using fish aggregating devices (FAD) as fishing aids.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fishermen utilize various fishing tools in Maluku, including purse seines, or what the Maluku people know better as jaring bobo. Purse Seine (jaring bobo) is a very productive fishing tool (Polhaupessy et al, 2019;Picaulima et al, 2022) and is found in almost every area in Maluku. The operation of this fishing gear is generally carried out by fishermen in Maluku using fish aggregating devices (FAD) as fishing aids.…”
Section: Introductionmentioning
confidence: 99%
“…The highest productivity of purse seine fisheries on Ambon Island, which is one of the islands in Maluku, during the fishing season and non-fishing season is 638 kg/trip and 288.6 kg/trip, respectively, while the productivity and number of crew members at both times is 36.1 kg/ABK and 16.6 kg/ABK (Polhaupessy et al, 2019). The average number of crew members who usually participate in fishing operations using purse seine fishing gear is 16-18 people (Picaulima et al, 2022), with different duties and responsibilities. The distribution of results in this business is usually carried out based on the fishermen's duties and responsibilities.…”
Section: Introductionmentioning
confidence: 99%